2018
DOI: 10.1038/s41567-018-0126-8
|View full text |Cite|
|
Sign up to set email alerts
|

Topological quantum phase transition in the Ising-like antiferromagnetic spin chain BaCo2V2O8

Abstract: Since the seminal ideas of Berezinskii, Kosterlitz and Thouless, topological excitations are at the heart of our understanding of a whole novel class of phase transitions. In most of the cases, those transitions are controlled by a single type of topological objects. There are however some situations, still poorly understood, where two dual topological excitations fight to control the phase diagram and the transition. Finding experimental realization of such cases is thus of considerable interest. We show here… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
124
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(139 citation statements)
references
References 40 publications
14
124
0
1
Order By: Relevance
“…Concomitantly, the continuum spectrum is replaced by a series of discrete spinon bound states. It has been found that the spinon confinement can be significantly tuned by applying a magnetic field [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Concomitantly, the continuum spectrum is replaced by a series of discrete spinon bound states. It has been found that the spinon confinement can be significantly tuned by applying a magnetic field [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…A new excitation of the longitudinal degree of freedom of the order parameter is predicted when the interchain coupling is weak [6]. These phenomena have been the subject of a considerable amount amount of recent experimental work in XXZ spin chain materials [11][12][13][14][15]. Like a similar longitudinal mode previously observed near the critical point in a system of coupled spin-1/2 dimers [16,17], this excitation can be interpreted as a condensed matter analog of the Higgs boson [18].…”
mentioning
confidence: 60%
“…The incommensurate phase shift α realizes the coexistence of the Néel order, 13) and the transverse dimer order (2.5). Their ground-state averages are given by…”
Section: B Non-abelian Bosonizationmentioning
confidence: 99%
“…Thanks to the dimensionality and strong interactions among elementary excitations, the excitation gap and the Néel order exhibit interesting power-law behaviors that deviate from spin-wave predictions [9,10,12]. The phenomenon of the field-induced excitation gap has drawn attention for its connection with confinement of topological excitations [13,14].…”
Section: Introductionmentioning
confidence: 99%